Community pharmacy role in children's health in England: Experiences and opinions of parents and young people. (21st March 2022) - Rashed, Asia N.; Mohamud, Nadiya; Lam, Alexander; Hamadallah, Hanaa; Terry, David; Tomlin, Stephen
Abstract: Little is known about the reason behind the underutilisation of community pharmacy (CP) for children. This study explored the experiences, barriers and recommendations of parents/carers and young people regarding their use of CP services for children. Two‐stage facilitated, structured, audio‐recorded interviews were conducted at each of four CPs in London, England, between May and November 2019 [1 month in each CP]. Parents/carers or young persons (aged 16–18 years) who visited CP for a child‐related matter were invited to participate. Interviews were transcribed verbatim. Data were analysed both quantitatively and qualitatively, using thematic analysis to identify themes. In total, 249 (58.2% of 428 eligible) customers agreed to participate and completed the two interviews. Out of these, 82.3% (205/249) reported positive experiences with the CP. The general practitioner (GP) was the preferred healthcare provider for minor ailments (44.6%, 111/249), while 35.7% (89/249) would choose CP. Eighty‐two participants (33%) visited an Emergency Department in the last 12 months, with 13.4% (11/82) of them visited for cold and cough reasons. Where a child was present with parents/carer (128/249), there was a low level of interaction between children and pharmacists (13.3%, 17/128). Lack of awareness about the CP services provided for children and privacy were among the barriers identified by participants. Advertising of CP services and creating a child‐friendly environment were recommendations suggested by participants. The findings of this paper show that CP remains an underutilised health service for children by parents/carers and young persons. More work is needed to increase public awareness of the roles of CP in children's health and well‐being.